Ultima Ratio as a Constitutional Principle - Tuori, Kaarlo (Oñati Socio-Legal Series, 2013)
The paper argues the criminal law notion of ultima ratio is an instance of a broader constitutional law principle of proportionality. However, ultima ratio is not the only principle relevant in a constitutional assessment of criminalization. The role of ultima ratio is to impose limitations on criminalization. But constitutional doctrines also exist which call for criminalization and might even be seen as establishing a criminalization obligation. The paper examines three constitutional counter weights to ultima ratio. The first of these is discussed in the context of state constitutions. This is the cluster of the interrelated constitutional doctrines of the horizontal effect of fundamental rights and the protective duty of the state, as well as the understanding of collective security as a basic right. These doctrines are analysed in the light of the praxis of the German Constitutional Court and the Finnish Constitutional Law Committee. The two other constitutional counterweights are discussed at the level of the transnational, European constitution. These are the principles of precaution and effectiveness.